Decoupling the Effect of Climate and Land-Use Changes on Carbon Sequestration of Vegetation in Mideast Hunan Province, China - Cong Liu (MDPI AG, 2021)
Urbanization and global climate change are two important global environmental phenomena in the 21st century. Human activities and climate changes usually increase the uncertainties of the ecosystem functions and structures and can greatly affect regional landscape patterns and the carbon cycle. Consequently, it is critical to understand how various climate and land-use changes influence the carbon dynamics at a regional scale. In this study, we quantitatively analyzed the spatial and temporal changes of net primary productivity (NPP) and the effects of climate factors and human disturbance factors (i.e., land-use changes) on the “Chang–Zhu–Tan” (CZT) urban agglomeration region from 2000 to 2015. The Carnegie–Ames–Stanford Approach (CASA) model was combined with spatially explicit land-use maps, monthly climate data, and MODIS NDVI images to simulate the carbon dynamics in the CZT area. Based on our six different scenarios, we also analyzed the relative roles of climate change and land-use change in total production. Our results indicated that the annual NPP of the study area maintained an upward trend by 7.31 gC•m−2•yr−1 between 2000 and 2015. At the same time, the average annual NPP was 628.99 gC•m−2 in the CZT area. We also found that the NPP was lower in the middle of the north region than in others. In addition, land-use changes could contribute to a positive effect on the total production in the study area by 3.42 T gC. Meanwhile, the effect of climate changes on the total production amounted to −1.44 T gC in the same region and period. Temperature and precipitation had negative effects on carbon sequestration from 2000 to 2015. As forest land constituted over 62.60% of the total land use from 2000 to 2015, the negative effect of carbon sequestration caused by urbanization could be ignored in the CZT area. Although climate and land-use changes had simultaneously positive and negative effects during the period 2000–2015, prioritizing the protection of existing forest land could contribute to increasing carbon sequestration and storage at the regional scale. Our study assists in understanding the impact of climate changes and land-use changes on carbon sequestration while providing a scientific basis for the rational and effective protection of the ecological environment in mid-east Hunan Province, China.